Genome sequencing and annotation of Aeromonas sp. HZM - Chua, P.; Har, Z.; Austin, C.; Yule, C.; Dykes, Gary; Lee, S. (2015)
We report the draft genome sequence of Cellulomonas sp. HZM, isolated from a tropical peat swamp forest. The draft genome size is 3,559,280 bp with a G + C content of 73% and contains 3 rRNA sequences (single copies of 5S, 16S and 23S rRNA).